Peran Hukum dalam Pengelolaan dan Perlindungan Lahan Gambut - Nuriyatman, Eko; Budhiartie, Arrie; Amir, Latifah (JURNAL USM LAW REVIEW, 2025)
This article aims to evaluate the effectiveness of the implementation of legislation in the management and protection of peatlands in Tanjung Jabung Timur Regency, as well as to identify the main obstacles and legal strategies that can be applied to overcome them. The background of the issue highlights that peatlands have significant ecological functions, particularly in maintaining environmental balance and mitigating climate change. Their existence faces serious threats due to land conversion, fires, and uncontrolled exploitation. The urgency of this research lies in the need to review the effectiveness of the regulations that have been implemented to ensure the sustainability of the peatland ecosystem functions, as well as the balance between utilization and environmental conservation. This research adopts a normative juridical approach with a descriptive-analytical method. The data used consists of secondary data obtained through a literature study of legislation, court decisions, scientific journals, and relevant policy documents. The novelty of this study lies in its specific focus on examining the implementation of legal regulations in peatland management in Tanjung Jabung Timur Regency, differing from previous studies that have been more general at the national level. The research findings indicate that the main obstacles in the implementation of peatland management laws include weak law enforcement, regulatory overlaps, conflicts of interest, and low public legal awareness. To address these challenges, optimal strategies are required, including strengthening coordination among state institutions, harmonizing regulations, enforcing strict sanctions, and utilizing technology for monitoring and law enforcement. With these strategies, it is expected that a balance between the utilization and protection of peatlands can be achieved in accordance with the principles of sustainable development.   Artikel ini bertujuan untuk mengevaluasi efektivitas implementasi peraturan perundang-undangan dalam pengelolaan dan perlindungan lahan gambut di Kabupaten Tanjung Jabung Timur serta mengidentifikasi hambatan utama dan strategi hukum yang dapat diterapkan guna mengatasinya. Latar belakang permasalahan menunjukkan bahwa lahan gambut memiliki fungsi ekologis yang signifikan, terutama dalam menjaga keseimbangan lingkungan dan mitigasi perubahan iklim. Keberadaannya menghadapi ancaman serius akibat konversi lahan, kebakaran, serta eksploitasi yang tidak terkendali. Urgensi penelitian ini terletak pada perlunya peninjauan efektivitas regulasi yang telah diterapkan untuk memastikan keberlanjutan fungsi ekosistem gambut serta keseimbangan antara pemanfaatan dan konservasi lingkungan. Penelitian ini menggunakan pendekatan yuridis normatif dengan metode deskriptif-analitis.  Kebaruan penelitian ini terletak pada fokusnya yang secara spesifik menelaah implementasi hukum dalam pengelolaan lahan gambut di Kabupaten Tanjung Jabung Timur, berbeda dari kajian sebelumnya yang lebih bersifat umum pada tingkat nasional. Hasil penelitian menunjukkan bahwa kendala utama dalam implementasi hukum pengelolaan lahan gambut meliputi lemahnya penegakan hukum, tumpang tindih regulasi, konflik kepentingan, serta minimnya kesadaran hukum masyarakat. Untuk mengatasi hambatan tersebut, diperlukan strategi optimal berupa penguatan koordinasi antar lembaga negara, harmonisasi regulasi, penerapan sanksi tegas, serta pemanfaatan teknologi dalam pengawasan dan penegakan hukum. Dengan strategi ini, diharapkan keseimbangan antara pemanfaatan dan perlindungan lahan gambut dapat terwujud sesuai dengan prinsip pembangunan berkelanjutan.